2017
DOI: 10.1007/s10899-016-9666-y
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Delivery of Cognitive Behaviour Therapy Compared to Monitoring, Feedback and Support for Problem Gambling: A Randomised Controlled Trial

Abstract: The aim of this study was to investigate the efficacy of an Internet-based cognitive behavioural therapy program (I-CBT) for the treatment of problem gambling, when compared to a waitlist control and an active comparison condition consisting of monitoring, feedback, and support (I-MFS). Participants (N = 174) were randomly allocated to the three conditions. Variables of interest were gambling outcome and related mental health measures. Participants in the active conditions (I-CBT and I-MFS) completed six onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(104 citation statements)
references
References 27 publications
5
97
0
2
Order By: Relevance
“…Nonetheless, the moderator analyses revealed more effective SH options providing support for high-intensity, structured Internet-based programs with MI and CBT elements (Carlbring & Smit, 2008; Casey et al., 2017). The effect size is equivalent to that obtained from FTFTs.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the moderator analyses revealed more effective SH options providing support for high-intensity, structured Internet-based programs with MI and CBT elements (Carlbring & Smit, 2008; Casey et al., 2017). The effect size is equivalent to that obtained from FTFTs.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that Internet-based CBT delivered comparable reductions in gambling amount, gambling frequency and, improved gambling refusal efficacy. However, lower dropout rates (18.6% vs. 47.7% and lower faulty gambling cognitions were observed in the face-to-face program [10].…”
Section: Principle Findingsmentioning
confidence: 76%
“…The convenience of Internet-based interventions may also contribute to the lack of program completion and online counselling or self-help programs may only be engaged in for as long as the consumer feels they are necessary [9]. One study compared the results of an Internet-based CBT program and found a substantially higher dropout rate (47.7%) compared to a similarly structured face-to-face program [10] Another potential limitation of Internet based interventions is that it is difficult to establish rapport in the same way as face-to-face interactions between consumers and providers. Rapport is an important component of effective treatment from both the perspective of the health professional and the client.…”
Section: Principle Findingsmentioning
confidence: 99%
“…Una possibile spiegazione può essere legata alla relativa facilità di accesso al servizio: spesso la registrazione è mossa più da impulsività e curiosità che da una reale motivazione al cambiamento. Considerato l'alto rischio di interruzione dai trattamenti online evidenziato in letteratura (Melville et al 2010), ulteriori ricerche dovrebbe aiutare a comprendere e prevenire i dropout in questa tipologia terapeutica (Casey et al, 2017).…”
Section: Discussioneunclassified